3D Generation of Multipurpose Atomic Force Microscopy Tips. Issue 27 (19th July 2022) - Glia, Ayoub; Deliorman, Muhammedin; Qasaimeh, Mohammad A.
Abstract: In this work, 3D polymeric atomic force microscopy (AFM) tips, referred to as 3DTIPs, are manufactured with great flexibility in design and function using two‐photon polymerization. With the technology holding a great potential in developing next‐generation AFM tips, 3DTIPs prove effective in obtaining high‐resolution and high‐speed AFM images in air and liquid environments, using common AFM modes. In particular, it is shown that the 3DTIPs provide high‐resolution imaging due to their extremely low Hamaker constant, high speed scanning rates due to their low quality factor, and high durability due to their soft nature and minimal isotropic tip wear; the three important features for advancing AFM studies. It is also shown that refining the tip end of the 3DTIPs by focused ion beam etching and by carbon nanotube inclusion substantially extends their functionality in high‐resolution AFM imaging, reaching angstrom scales. Altogether, the multifunctional capabilities of 3DTIPs can bring next‐generation AFM tips to routine and advanced AFM applications, and expand the fields of high speed AFM imaging and biological force measurements. Abstract : Multipurpose polymeric atomic force microscopy (AFM) tips, named 3DTIPs, are presented with low Hamaker constant for high resolution, high speed AFM imaging. The 3DTIPs are generated with great flexibility in design, material, and function allowing better control over resonance frequency, quality factor, and spring constant. Their tip ends are further post‐processed to extend their functionality in high resolution AFM imaging.